PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 1 SAKRA BARAT TAHUN PELAJARAN 2016/2017 - Sabrun, Sabrun (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
The subjects of this study are students of class VIII A which amounted to 35 people. This classroom action research consists of 2 cycles, each cycle consisting of the planning stage, action implementation, observation, and reflection. Based on the result of observation analysis of student activity on cycle I meeting I got total score and average as much 37 and 2.31 categorized